2021
DOI: 10.1007/s40744-021-00288-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6, CA19-9, CA125 and CEA are Diagnostic Biomarkers for Rheumatoid Arthritis-Associated Interstitial Lung Disease in the Chinese Population

Abstract: Introduction This study aimed to evaluate the role of tumor marker carbohydrate antigen (CA) 125 (CA125), CA19-9, carcinoembryonic antigen (CEA) and Krebs von den Lungen-6 (KL-6) in the diagnosis and determination of the severity of interstitial lung disease (ILD) in rheumatoid arthritis (RA) patients. Methods A retrospective analysis was performed. Fifty RA patients (24 patients with ILD and 26 patients without ILD), 10 healthy subjects and 14 patients with other conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“… 22 Zheng et al reported that the serum levels of CA19-9, CA125 and CEA were also elevated in RA-ILD and showed a strong association with the severity of the disorder. 16 Similarly, Shi et al showed that SS-ILD patients had elevated serum levels of tumor markers, including NSE, CEA, CA125, and CA153, 18 while Wong et al reported that IM-ILD patients without cancer had elevated levels of CA153. 19 Sargin et al considered that RA patients with an increase in tumor markers especially CA153 and CA125 should be suspected of having an ILD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Zheng et al reported that the serum levels of CA19-9, CA125 and CEA were also elevated in RA-ILD and showed a strong association with the severity of the disorder. 16 Similarly, Shi et al showed that SS-ILD patients had elevated serum levels of tumor markers, including NSE, CEA, CA125, and CA153, 18 while Wong et al reported that IM-ILD patients without cancer had elevated levels of CA153. 19 Sargin et al considered that RA patients with an increase in tumor markers especially CA153 and CA125 should be suspected of having an ILD.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 The value of tumor markers for investigating ILDs has also been supported by the findings of several recent studies, especially for diagnosing and evaluating the risk of developing this condition. 16–20 …”
Section: Introductionmentioning
confidence: 99%
“…Even the tumour markers CA (carbohydrate antigen)-125 and CA19-9 have been studied as markers of epithelial damage and can predict short-term mortality [ 40 ]. Similarly, in RA-ILD, CA125, CA19-9, CEA (carcinoembryonic antigen), and KL-6 have been validated as biomarkers [ 41 ]. Other biomarkers for RA-ILD can include genetic polymorphisms of the MUC5B gene and serum interleukin-13 levels [ 20 , 42 ].…”
Section: Screening Monitoring and Diagnosismentioning
confidence: 99%
“…Additionally, the development of tumor markers may also contribute to ILD; their diagnostic utilities have been investigated. The levels of carbohydrate antigen (CA) 19–9, CA125, CEA, and CA15-3 were increased compared to a control group of RA-non-ILD patients [ 12 , 13 ]. D-dimer is the end-product of cross-linked fibrinolysis and is involved in the acute phase of inflammation; it may thus contribute to the pathophysiology of RA-ILD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%